2017
DOI: 10.1007/s00330-017-4788-x
|View full text |Cite
|
Sign up to set email alerts
|

CT perfusion imaging of the liver and the spleen in patients with cirrhosis: Is there a correlation between perfusion and portal venous hypertension?

Abstract: ObjectivesTo correlate hepatic and splenic CT perfusion parameters with hepatic venous pressure gradient (HVPG) measurements in patients with cirrhosis.MethodsTwenty-one patients with cirrhosis (males, 17; females, 4; mean ± SD age, 57 ± 7 years) underwent hepatic and splenic perfusion CT on a 320-detector row volume scanner as well as invasive measurement of HVPG. Different CT perfusion algorithms (maximum slope analysis and Patlak plot) were used to measure hepatic arterial flow (HAF), portal venous flow (PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
2
21
4
1
Order By: Relevance
“…The published data on spleen perfusion quantification in PH is limited, with variable results . The absence of correlation between spleen blood flow and HVPG is not in accordance with two previous studies, which found a decrease of splenic blood flow in PH . Similarly, a relationship between spleen K trans and HVPG was also observed previously, but not reproduced in our study .…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…The published data on spleen perfusion quantification in PH is limited, with variable results . The absence of correlation between spleen blood flow and HVPG is not in accordance with two previous studies, which found a decrease of splenic blood flow in PH . Similarly, a relationship between spleen K trans and HVPG was also observed previously, but not reproduced in our study .…”
Section: Discussioncontrasting
confidence: 95%
“…None of the spleen DCE‐MRI parameters correlated with HVPG measurements, with only a trend found for spleen TTP. The published data on spleen perfusion quantification in PH is limited, with variable results . The absence of correlation between spleen blood flow and HVPG is not in accordance with two previous studies, which found a decrease of splenic blood flow in PH .…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations